High-performance self-powered UV photodetectors using SnO2 thin film by reactive magnetron sputtering - Kumar, Mahesh; Saravanan, Adhimoorthy; Joshi, Shikha Akshay; Chen, Sheng-Chi; Huang, Bohr-Ran; Sun, Hui (Sensors and actuators. A. Physical., 2024)
Self-powered UV photodetector (UVPD) operates without the need for an external energy source and contributes to global energy conservation. With ongoing innovation, self-powered PDs are becoming increasingly appealing for industrial and innovation applications such as advanced environmental monitoring and communication devices. This study investigates the influence of varying working pressures (ranging from 3 to 15 mTorr) during reactive magnetron sputtering on the crystalline structure, surface morphology, and performance of SnO2 thin film photodetectors, aiming to fabricate self-powered UVPDs. The SnO2-based UVPD demonstrates exceptional self-powered UV photodetection capabilities, characterized by a sensitivity of 6.41×105%, responsivity of 0.09 mA/W, and detectivity of 2.99×1010 Jones. In addition, SnO2-based UVPD possesses a switching photo response and recovery time of 0.75 and 0.99 s. Henceforth, it was observed that 8 mTorr SnO2 thin film exhibits exceptional stability, superior photodetector performance, and remarkable repeatability, rendering them highly suitable for UVPD applications. Notably, these films demonstrate sustained functionality for approximately 100 days without necessitating encapsulation. These excellent results confirm that SnO2 thin films are suitable for fabricating future smart optoelectronics devices. [Display omitted] •R-DCMS technique-derived SnO2 films for self-power photodetection applications.•The SnO2 photodetector show outstanding self-powered UV photodetection performance.•SnO2-based UVPD show fast response and recovery time of 0.7 and 0.9 s.•The SnO2 UV photodetector offers repeatability for around 100 days.